Paul Virilio : from modernism to hypermodernism and beyond - Armitage, John, 1956- (Published in association with Theory, Culture & Society., 2000)
An examination of Virilio's work on cultural theory; includes an interview with Virilio; a recently translated example of his work; and a select bibliography of his writings.